Perancangan Alat Pemberi Makan Hewan Otomatis dengan Sensor Ultrasonik dan Teknologi Mikrokontroler - Tarrosa, Bayu Asta; Ramadhan, Bilal; Hafizh, Kemas M.; Anugrah, M. Rifky; Muslimin, Muslimin; Luqyana, Dhiya; Muhamad, Azam Milah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Along with the advancement of technology and the increasing busyness of everyday people, the need for tools to help with daily activities is becoming increasingly important, including for pet owners such as cats. This study designs an automatic tool called